Birds of prey : and the fantabulous emancipation of one Harley Quinn [videorecording (DVD)] - Robbie, Margot, 1990-; Perez, Rosie; Winstead, Mary Elizabeth; Smollett-Bell, Jurnee, 1986-; McGregor, Ewan, 1971- (Warner Bros. Home Entertainment, 2020)
After splitting with the Joker, Harley Quinn joins superheroes Black Canary, Huntress and Renee Montoya to save a young girl from an evil crime lord.